Conversion of De Laval Coco Protein into soluble form as stabilizer and other food uses - Celestino, V.G; Gonzales, A.L; Capulso, S.A (1981)
The possible solubilization of de-laval solid, a by-product of the wet-processing of coconut, into a soluble coc-proteinate suitable as emulsifier/stabilizer or as food additive has been investigated. The protein solid with 74-77% protein content makes it a good source of protein, although it has low solubility characteristic. Solubility of the protein solid in different solvents was determined the maximum solubility occurred at pH range 11-12; H20-2.5%, 70% alcohol-1.22%, 1% Na2S04-1.58%, and 1% Na0H-42.31%. Conversion of the defatted protein to soluble form was patterned after the dairy milk protein solubilization method (US Patent, 2,832,685). The composition and amino acid analyses of the prepared K coco proteinate compared favorably with that of Na caseinate except the former has higher arginine content. The results on emulsification properties of the prepared proteinate indicated its inability to completely function as an emulsifier. The addition of sodium chloride and sucrose did not increase its emulsifying property.